2017
DOI: 10.3329/jbcps.v35i4.34735
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception about Status of Bedside Teaching in Undergraduate Medical Education of Bangladesh

Abstract: Introduction: Bedside teaching is the core teaching strategy in the clinical study in undergraduate medical education of Bangladesh. Many of the environments and opportunities available for bedside teaching and learning have changed. Students’ views about current status of bed side teaching in Obstetrics and Gynaecology was studied in this study.Methodology: This was a cross sectional study conducted in seven (three public and four private) medical colleges in Bangladesh from July 2012 to June 2013. A total 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Highest mean score among 4 domains was for patient’s comfort and attitude towards patient (3.87) and only stem with less than three score was failure to explain findings to patient (2.91). Similar student’s feedback was noted by Sultana J et al 17 She believes that high scores in domain of student’s attitude towards patients depicts their inability to be impartial in self-evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…Highest mean score among 4 domains was for patient’s comfort and attitude towards patient (3.87) and only stem with less than three score was failure to explain findings to patient (2.91). Similar student’s feedback was noted by Sultana J et al 17 She believes that high scores in domain of student’s attitude towards patients depicts their inability to be impartial in self-evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…This result is in corroboration with a Bangladeshi research where this attribute was found to be taught to medical students in detail. 16 This study highlights a high response (90%) related to effectiveness of this teaching method suitable for learning evidence based medicine. However, this finding is not in accordance with the work of Nair et al, where the rate was 65% only.…”
Section: Discussionmentioning
confidence: 81%
“…This is congruous with a study in Bangladesh except differences in communicating findings to patients where mean score in this study was reported less than 3. 14 For teaching sessions, mean score and mean score of most individual responses was more than 3. There was lack of opportunity to examine patients in teaching sessions at two private institutes where mean score was less than 3.…”
Section: Methodsmentioning
confidence: 96%
“…First questionnaire used consisted of 12 items 4 points Likert scale with little modification from a paper published in Bangladesh. 14 These 12 items were further categorized into two subscales in order to measure physical environment of bedside teaching, patients' comfort and students' attitude towards patients. The second questionnaire which was used for this study consisted of 18 items 5-points Likert scale which was also adopted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation